Pharmacognostic and Phytochemical screening of Cowpea seeds (Vigna unguiculata) - Ramesh L Londonkar,; Basavarajeshwari S Awanti, (International Journal of Phytomedicine, 2014)
Vigna unguiculata (Cow pea) is well known medicinal plant. The drug isolated from this plant is used in different science of medicines like, ayurveda, unani, sidda, allopathic, homeopathic and naturopathic therapy. The present investigation deals with pharmacognostic and phytochemical screening of the seeds of Vigna uguiculata. The pharmacognostic studies include physicochemical constant and fluorescence analysis. The petroleum ether, chloroform, methanol and aqueous extracts are subjected to preliminary phytochemical screening. The physicochemical constants obtained were found to be within normal levels prescribed by phytochemical standards. The phytochemical studies of seeds of Vigna uguiculata revealed the presence of primary and secondary metabolites like proteins, carbohydrates, glycosides, phenols,flavonoids, saponins, sterols and alkaloids. The flavonoid content of methanol extract was found to be 621± 2.494 µg rutin/g. These studies provide a referential information for identification of this crude drug and the results are helpful for the isolation of medicinally important active components.